Análisis del sistema eléctrico en la fábrica productora de gelatina ecuatoriana Prodegel S.A., para determinar el esatado actual de las instalaciones eléctricas. - Fiallos Pillajo, Byron Patricio (2017)
This research in PRODEGEL.S.A Factory located in Totoras Parish is made for the analysis of the power system, with the purpose of determining the variations of the energy flow produced by the lack of control of the electrical installations in the industry, so it is proposed to fulfill the objectives proposed: to develop an analysis process of the electrical system of the main magnitudes of energy in the factory and update the single-line scheme including new Dry Zone facilities, that is an area where the product process is completed; to determine the current state of the power flow facilities by a behavior analyzing of the different electrical variables; to establish the results by a technical evaluation through a development of the electrical system analysis. Also, quantitative and qualitative methodological approaches were used in the methodology, the primary research modalities, levels and types of research, based on the electrical system analysis of the factory to identify if the maintenance of the facilities is carried out to verify the variations of the power flow and the consequences that this can cause in the machinery and equipment which the PRODEGEL.SA has to, which will allow making a proposal that will determine by an implementation of the electrical system to improve its functionality, all these activities will contribute to enhance the electric control inside the factory.